FMRI studies prior and post acupuncture treatment concerning smoking cessation. (September 2016) - Theodoratou, K.; Christidi, F.; Toulas, P.; Verganelakis, D.A.
Abstract : Introduction: Acupuncture has been widely reported to be a popular and safe intervention for smoking cessation. This study demonstrates the potential effects of acupuncture treatment for smoking cessation using the MRI technique of functional Magnetic Resonance Imaging (fMRI). Purpose: Substance dependence or addiction is nowadays uderstood in a multifactorial etiological model, which includes psychological, neurobiological, genetic, social and environmental factors. This study illustrates patterns of fMRI activation in various specific brain anatomies, such as frontal, temporal parietal, occipital and cerebellum that correlate with smoking. Materials and methods: Participants of both genders were volunteers willing to quit smoking. The inclusion criteria were age (28–42 y) and rate of smoking >15 cigarrettes per day and had no previous experience of acupuncture treatment. Group A received real acupuncture, Group B sham acupuncture and Group C was the control group with no smokers. Acupuncture points used: Du-20, LI-20, LI-4, TB-5, ST-36, LIV-3 and treatments lasted for 20 min. fMRI was applied prior and post acupuncture treatment during the first 24 hours of smoking cessation. During the fMRI experiment a series of smoking related images were presented to each participant via a set of goggles in a block time-design manner. Results: Increased brain response areas were observed, such as: dorsolateral prefrontal, primary motor gyrus, parahippocampal gyrus, hippocampus, insula, posterior cingulate cortex, somatosensory cortex, visual areas and external basal ganglia. Differences between Groups A and B, as well as interesting correlations between acupuncture points, fMRI findings and neurobiological areas are presented. Conclusion: Our results provide evidences over a pattern of slightly different brain activation following real and sham acupuncture after a short term smoking abstinence. The observed differences are in areas involved in drug addiction and smoking maintenance/abstinence literature.